Gender Diversity in Jordan : Research on the Impact of Gender Diversity on the Economic Performance of Companies in Jordan - International Finance Corporation (International Finance Corporation, Washington, DC, 2017)
Increasing women’s participation on corporate boards and in senior management is among the crucial requirements of companies all around the world. IFC is no exception. The authors have seen for ourselves the positive results from greater diversity in corporate leadership. Stated simply, gender balance is good for business. The participation of women in the labor market has been a major driver of growth and competitiveness in economies. Yet, when it comes to corporate leadership positions, there remains a huge gap between the numbers of men and women represented. In Jordan this is no different. Men have assumed the highest positions of corporate leadership, even as women represent a strong untapped asset for the country. Despite constituting a large portion of society in Jordan, women have a minor presence in boardrooms and in senior decision-making positions. The research in this publication sets out to demonstrate: the degree of involvement by women in boardrooms and senior decision-making positions in the corporate world; the value of their presence when they are involved in those positions (specifically whether there is a correlation between women in the boardroom and the financial performance of companies); and some of the challenges that women face in reaching such decision-making positions. The publication also includes some recommendations for ways to overcome those challenges.